(3GdJLGQI YHQ GdGfJQfJs - (3YHO GdaJGM Hjhej(B, (3MLGRjs ((3GdGScfOQjI(B:s (3OGQ GdacQ GdLGeYj(B,s, 2007)
(3jJfGhd gPG GdcJGH eGjdj ebOeI YGeI(B- (3GdbSe GdGhd (B: (3eTcdGJ ai GdJLGQI GdGdcJQhfjI YHQ GdGfJQfJ (B: (3GdaUd GdGhd (B: (3GdeSJgdc ai fWGb GdJLGQI GdGdcJQhfjI (B: (3GdaUd GdKGfi (B: (3JTajQ GdHjGfGJ hGdeYdheGJ ai fWGb GdJLGQI GdGdjcJQhfjI (B: (3GdeHMK GdGhd (B: (3GdJYQja HGdJTajQ (B: (3GdeHMK GdKGfi (B: (3WQb GdJTajQ (B: (3GdaUd GdKGdK (B: (3GSeGA GdOhejf ai fWGb GdJLGQI GdGdjcJQhfjI (B: (3GdeHMK GdChd (B: (3JSLjd GdYdGeGJ GdJLGQjI hCSeGA GdOhejjf (B: (3GdeHMK GdKGfj (B: (3TQhW GdYdGeGJ GdJLGQjI hcPdc CSeGA GdOhejjf (B: (3GdaUd GdQGHY (B: (3GdbGfhf GdhGLH GdJWHjb hGdeMceI GdeNJUI (B: (3GdeHMK GdGhd (B: (3eUGOQ GdbGYOI GdbGfhfjI ai GdJLGQI GdOhdjI (B: (3GdeHMK GdKGfj (B: (3GdbGfhf GdhGLH GdJWHjb(B- (3GdbSe GdKGfi (B: (3JWHjb bGfhf GdeYGedGJ hGdJLGQI GdGdjcJQhfjI ai OhdI GdGeGQGJ GdYQHjI GdeJMOI (B: (3GdaUd GdGhd (B: (3JYGQja heUWdMGJ (B: (3GdaUd GdKGfi (B: (3SQjGf GdbGfhf (B: (3GdaUd GdKGdK (B: (3eJWdHGJ GdeYGedGJ GdGdjcJQhfjI (B: (3GdaUd GdQGHY (B: (3GdeYGedGJ GdGdjcJQhfjI ai fWGb GdJLGQI GdGdjcJQhfjI (B: (3GdaUd GdNGeS (B: (3GdSLdGJ GdGdjcJQhfjI GdeMejI (B: (3GdaUd GdSGOS (B: (3GdGMcGe GdeJUdI HGdTgGOGJ hNOeGJ GdJUOjb (B: (3GdaUd GdSGHY (B: (3GdGYJQGa HGdTgGOGJ hGdJhbjYGJ GdGdjcJQhfjI GdGLfHjI (B: (3GdaUd GdKGef (B: (3GdGSJNOGe GdMchei ddSLdGJ hGdJhbjYGJ GdGdjcJQhfjI (B: (3GdaUd GdJGSY (B: (3GdMeGjI GdLfGFjI ddJLGQI hGdeYGedGJ GdGdjcJQhfjI ai GdbGfhf(B.s
(3HjHdjhZQGajG U(B.367s
Keywords: (3GdGfJQfjJs; (3GdJLGQI GdGdcJQhfjIs; (3GdJLGQI GdNGQLjIs; (3GdJLGQI YH GdNWs; (3GfJQfJs